Clinical Trials Evaluating Drug Therapy: Types, Reliability of Results, Place in Modern Evidence-Based Medicine - S. Yu. Martsevich; N. P. Kutishenko; Yu. V. Lukina; M. M. Lukyanov; O. M. Drapkina (Рациональная фармакотерапия в кардиологии, 2021)
The article discusses the main methods of evidence in modern medicine. Special attention is paid to randomized controlled trials and observational studies. The advantages of randomized controlled trials over observational studies are considered. A comparison of the informative value of randomized controlled trials and observational studies in assessing the effect of therapeutic interventions is made. Attention is drawn to situations when conducting randomized controlled trials is not possible and when they become the main source of information. It is emphasized that in order to verify the results of randomized controlled trials in real clinical practice, it is necessary to conduct observational studies. The basic principles of conducting observational studies are considered.